2014
DOI: 10.1176/appi.ajp.2014.14010094
|View full text |Cite
|
Sign up to set email alerts
|

An Inflammatory Biomarker as a Differential Predictor of Outcome of Depression Treatment With Escitalopram and Nortriptyline

Abstract: An easily accessible peripheral blood biomarker may contribute to improvement in outcomes of major depressive disorder by personalizing treatment choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
259
6
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(283 citation statements)
references
References 55 publications
14
259
6
4
Order By: Relevance
“…Although the promise of anti-inflammatory pharmacological agents for the treatment of chronic psychopathology has gained traction based on the work done with regard to depression (Raison et al, 2013;Uher et al, 2014), other forms of intervention could prove efficacious in dampening inflammatory processes in fear-and anxiety-based disorders. Cognitive and behavioral interventions, including prolonged exposure, are effective treatments for fear-and anxiety-based disorders (Butler et al, 2006;Powers et al, 2010), but it still remains unclear whether these treatments also reduce inflammation.…”
Section: Treatment Implications and Future Directionsmentioning
confidence: 99%
“…Although the promise of anti-inflammatory pharmacological agents for the treatment of chronic psychopathology has gained traction based on the work done with regard to depression (Raison et al, 2013;Uher et al, 2014), other forms of intervention could prove efficacious in dampening inflammatory processes in fear-and anxiety-based disorders. Cognitive and behavioral interventions, including prolonged exposure, are effective treatments for fear-and anxiety-based disorders (Butler et al, 2006;Powers et al, 2010), but it still remains unclear whether these treatments also reduce inflammation.…”
Section: Treatment Implications and Future Directionsmentioning
confidence: 99%
“…In mood disorders, several studies have suggested that the chronic mild inflammation indicated by elevated C-reactive protein (Courtet et al, 2015;Rapaport et al, 2015;Uher et al, 2014) as well as the quantification of the levels of inflammatory cytokines such as IL-6, IL-10 and TNF (de Witte et al, 2014;Ducasse et al, 2015b;Haapakoski et al, 2015;Halaris et al, 2015;Rethorst et al, 2013) could prove to be useful biomarkers for improved diagnosis and the detection of treatment refractoriness (Strawbridge et al, 2015), as well as indicators of the risk of suicide. As an increasing number of inflammatory factors are tested, an emerging picture supports the idea that a complex network of cytokines is involved in the pathophysiology of disease such as major depression (Dahl et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly and importantly, the depressed patients who are non responders to antidepressant therapies or who are treatment resistant show higher plasma concentrations of several proinflammatory cytokines as compared to responders 35,36 . To add to the conclusions, cytokine expression in the leukocytes from depressed patients are reduced following escitalopram and nortriptyline treatment with a significant correlation between these changes and treatment response.…”
Section: Cytokine Hypothesis and Depressionmentioning
confidence: 99%